HER2-encoded mir-4728 forms a receptor-independent circuit with miR-21-5p through the non-canonical poly(A) polymerase PAPD5 - Newie, Inga; Søkilde, Rolf; Persson, Helena; Jacomasso, Thiago; Gorbatenko, Andrej; Borg, Åke; de Hoon, Michiel; Pedersen, Stine F.; Rovira, Carlos (Scientific reports, 2016)
We previously reported that the human HER2 gene encodes the intronic microRNA mir-4728, which is overexpressed together with its oncogenic host gene and may act independently of the HER2 receptor. More recently, we also reported that the oncogenic miR-21-5p is regulated by 3′ tailing and trimming by the non-canonical poly(A) polymerase PAPD5 and the ribonuclease PARN. Here we demonstrate a dual function for the HER2 locus in upregulation of miR-21-5p; while HER2 signalling activates transcription of mir-21, miR-4728-3p specifically stabilises miR-21-5p through inhibition of PAPD5. Our results establish a new and unexpected oncogenic role for the HER2 locus that is not currently being targeted by any anti-HER2 therapy.